Adults with excess weight or obesity, but not with overweight, report greater pain intensities than individuals with normal weight: a systematic review and meta-analysis - Garcia, Miguel M.; Corrales, Patricia; Huerta, Miguel Á.; Czachorowski, Maciej J.; López-Miranda, Visitación; Medina-Gómez, Gema; Cobos, Enrique J.; Goicoechea, Carlos; Molina-Álvarez, Miguel (Frontiers in Endocrinology, 2024)
Context. Over 1.9 billion adult people have overweight or obesity. Considered as a chronic disease itself, obesity is associated with several comorbidities. Chronic pain affects approximately 60 million people and its connection with obesity has been displayed in several studies. However, controversial results showing both lower and higher pain thresholds in subjects with obesity compared to individuals with normal weight and the different parameters used to define such association (e.g., pain severity, frequency or duration) make it hard to draw straight forward conclusions in the matter. The objective of this article is to examine the relationship between overweight and obesity (classified with BMI as recommended by WHO) and self-perceived pain intensity in adults. Methods. A literature search was conducted following PRISMA guidelines using the databases CINAHL, Cochrane Library, EMBASE, PEDro, PubMed, Scopus and Web of Science to identify original studies that provide BMI values and their associated pain intensity assessed by self-report scales. Self-report pain scores were normalized and pooled within meta-analyses. The Cochrane’s Q test and I2 index were used to clarify the amount of heterogeneity; meta-regression was performed to explore the relationship between each outcome and the risk of bias. Results. Of 2194 studies, 31 eligible studies were identified and appraised, 22 of which provided data for a quantitative analysis. The results herein suggested that adults with excess weight (BMI ≥25.0) or obesity (BMI ≥ 30.0) but not with overweight (pre-obesity) alone (BMI 25.0–29.9), are more likely to report greater intensities of pain than individuals of normal weight (BMI 18.5–24.9). Subgroup analyses regarding the pathology of the patients showed no statistically significant differences between groups. Also, influence of age in the effect size, evaluated by meta-regression, was only observed in one of the four analyses. Furthermore, the robustness of the findings was supported by two different sensitivity analyses. Conclusion. Subjects with obesity and excess weight, but not overweight, reported greater pain intensities than individuals with normal weight. This finding encourages treatment of obesity as a component of pain management. More research is required to better understand the mechanisms of these differences and the clinical utility of the findings.